Three Cases of Neoplastic Meningitis Initially Diagnosed with Infectious Meningitis in Emergency Department. (6th June 2013) - Ahn, Shin; Lim, Kyung Soo
Abstract : Neoplastic meningitis (NM) is diagnosed by the presence of malignant cells in the cerebrospinal fluid (CSF). We report 3 patients with NM, who were misdiagnosed with infectious meningitis in emergency department (ED). Case 1. A 68-year-old man visited our ED with a 3-month history of headache. With MRI and CSF study, he was diagnosed with tuberculous meningitis. After 20 days, repeated CSF cytology showed malignant cells. His diagnosis was lung cancer with NM. Case 2. A 57-year-old man visited regional hospital ED with a 3-week history of headache and diplopia. Brain MRI was not contributory. With CSF examination, his diagnosis was aseptic meningitis. With worsening headache, he was referred to our ED. Repeated CSF showed malignant cells. His diagnosis was stomach cancer with NM. Case 3. A 75-year-old man visited a regional hospital with headache lasting for 4 months. His diagnosis was sinusitis. Persistent symptom brought him back, and he developed recurrent generalized seizures. Brain MRI showed diffuse leptomeningeal enhancement suggesting meningitis, and he was transferred to our ED. CSF exam showed malignant cells. His diagnosis was NM with unknown primary focus. When evaluating the patients with headache in ED, NM should be kept in mind as a differential diagnosis of meningitis.